Determinants of engagement of rural women in non-farm economic activities in rural Ethiopia - Fasika Chekol (Cogent Social Sciences)
In Ethiopia, a sizable section of the rural population depends on agriculture for a living. However, because of low agricultural output, a large number of rural households experience chronic poverty and food insecurity. Unfortunately, mothers and women are shocked by the food shortage to feed their children and families. This means women participate in rural non-farm economic activities (RNFEA) to generate income and cope with these challenges. Thus, the study explored the determinants of women’s participation in RNFEA in the districts of Goncha Siso Enese and Enebsie Sar Midir, Amhara Region, Ethiopia. The study was based on survey data collected from 358 randomly chosen women in the four kebeles from the study district. Both descriptive and inferential statistics were employed to analyze the data. The result indicates that about 59% of the respondents are non-participants in RNFEA due to the negative cultural (95%) and social (90) factors: lack of transport and market infrastructure (59%), lack of experience and skill (43%) and a combination of all (26%). While the binary logistic regression result indicated that age, livestock size, land size, food shock and distance to the market significantly affect women’s participation in RNFEA; there is still a rich supply of female labor force participants who are underutilized in farming due to a lack of awareness creation, negative sociocultural factors and poor infrastructure. Solving these related problems can help transfer them to the non-farm sector, which may support the upgrading of rural industries and promote the implementation of rural revitalization.